Calibration of Chronic Lung Disease Severity as a Risk Factor for Respiratory Syncytial Virus Hospitalization. (26th September 2020) - Choi, Yoonyoung; Meissner, H Cody; Hampp, Christian; Park, Haesuk; Brumback, Babette; Winterstein, Almut G
Abstract: Background: Guidelines assume children with chronic lung disease (CLD) who require medical support within 6 months before the second respiratory syncytial virus (RSV) season remains at high risk of severe RSV disease. We determined the number of days since the last treatment (DSL) when the risk of RSV hospitalization among children with CLD becomes equivalent to the risk for those not qualified for immunoprophylaxis. Methods: The study cohort was assembled using Medicaid billing records from 1999 to 2010 linked to Florida and Texas birth certificate records. We developed DSL-trend discrete time logistic regression models within a survival analysis framework, adjusting for use of immunoprophylaxis, to compare the hospitalization risk of CLD infants at 4 age points to that of term infants at 1 month of age with siblings. Results: The study cohort included 858 830 healthy term and 5562 preterm infants with CLD. Among 1-month-old term infants, the RSV hospitalization risk averaged across all covariate strata was 14.8 (95% confidence interval [CI], 13.5–16.1) per 1000 patient season-months. Risk for preterm CLD children reached the threshold derived from term infants when DSL was 76 (95% CI, 22–198.5), 52 (95% CI, 6.5–123), 35 (95% CI, 0–93.5), and 12 (95% CI, 0–61.5) at the respective ages of 12, 15, 17.2, and 21 months. Conclusions: The 180-day threshold used to define CLD severity at season start can be shortened to 120 days, 90 days, and 60 days for children with CLD at age 15, 17.2, and 21 months, respectively. Abstract : The American Academy of Pediatrics' guidelines' 180-day threshold can be shortened for older children with CLD (120-day, 90-day, and 60-day thresholds for children aged 15, 17.2, and 21 months at the onset of the second RSV season, respectively).